Validation of the colostomy impact score in patients ostomized for a benign condition. (19th August 2020) - Kristensen, H. Ø; Krogsgaard, M.; Christensen, P.; Thomsen, T.
Abstract: Aim: The colostomy impact (CI) score is a patient‐reported outcome measure assessing reduction in health‐related quality of life (HRQL) due to a stoma. The score was originally developed and validated in a cohort of rectal cancer survivors with a permanent colostomy. For the CI score to be applied to patients with a colostomy after surgery for a benign condition it must be validated in this patient group. The aim of this study was to assess construct validity and known groups validity of the CI score in patients with a colostomy after surgery for a benign condition. Method: In a cross‐sectional survey among ostomates in the Capital Region of Denmark, patients completed the CI score and the SF‐36 v2 questionnaires. Construct validity was assessed by Pearson's correlation coefficients and known groups validity was assessed by t ‐test when dividing patients into groups of minor or major CI. Results: The CI score showed a moderate negative correlation with the Physical Component Summary (PCS) of −0.41 and a weak negative correlation with the Mental Component Summary (MCS) of −0.39. The strength of the correlation depended on the underlying condition leading to stoma formation. Differences were significant between the minor and major CI groups in mean PSC and MCS with t ‐values of 5.32 and 3.86, respectively. Conclusion: The CI score is a valid instrument for assessing stoma‐related impact on HRQL regardless of the underlying condition leading to stoma formation, and the CI score discriminates meaningfully between groups with known differences in stoma‐related reduced HRQL.